Clinical and laboratory characteristics of enteroviral meningitis in children, including qRT-PCR and sequencing analysis - Braunová, Adriana; Krbková, Lenka; Rainetová, Petra; Musílek, Martin; Čapovová, Iva; Klapačová, Lenka; Musil, Václav; Homola, Lukáš; Kravalová, Tamara; Bednářová, Jana; Kýr, Michal (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2019)
AIMS: Enteroviruses (EVs) are the most common agents of aseptic meningitis. Some serotypes can cause serious neuroinfection leading to death. The aim of this study was to determine the representation of EVs in the etiology of aseptic meningitis in children and to analyze the demographic, clinical, laboratory, and epidemiological characteristics of patients with EV meningitis. PATIENTS AND METHODS: This was a prospective study including 147 patients in three groups: EV meningitis, tick-borne encephalitis, and aseptic meningitis with unidentified agent. RESULTS: Boys with EV meningitis predominated over girls. The average patient age was 11 years. Compared to the control group, these patients suffered more from stiff back (P=0.010), vomiting and nausea (P=0.009). They had shorter symptom duration (P<0.001), higher C-reactive protein in blood (P<0.001), higher predominance of polynuclears (P=0.026), and greater lactate (P=0.003) in cerebrospinal fluid (CSF). The serotype seen most frequently (68%) was ECHO virus (ECV) 30. CONCLUSIONS: Enteroviruses play the most important role in the differential diagnosis of aseptic meningitis. Short symptom duration, slightly higher inflammatory parameters in blood, predominance of polynuclears, and elevated CSF lactate have predictive value in diagnosing this disease. ECV 30 (frequently the agent of epidemics in the Czech Republic) was the aseptic meningitis agent most often seen.
Keywords: Humans; Enterovirus Infections; dítě; Meningitis, Viral; Child; sekvenční analýza; Female; polymerázová řetězová reakce s reverzní transkripcí; Sequence Analysis; lidé; enterovirové infekce; Reverse Transcriptase Polymerase Chain Reaction; meningitida aseptická; předškolní dítě; Enterovirus; ženské pohlaví; Male; Adolescent; Czech Republic; meningitida virová; Meningitis, Aseptic; Česká republika; mužské pohlaví; prospektivní studie; Child, Preschool; mladiství; Prospective Studies